2022
DOI: 10.1155/2022/5062620
|View full text |Cite
|
Sign up to set email alerts
|

Research on Citizen Participation in Government Ecological Environment Governance Based on the Research Perspective of “Dual Carbon Target”

Abstract: As the people’s demand for a better life is getting higher and higher, citizens’ requirements for the rural ecological environment are also constantly improving. At present, the deterioration of many rural environments and the cross-flow of sewage have brought great challenges to the governance of the rural ecological environment. Therefore, the improvement in the ability and level of rural ecological environment governance is the key to winning the battle of rural ecological environment governance, and the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The dual-carbon micro-renewal of Changhua Street not only requires a suitable spatial design, but also guidance in the entire decision making, design, implementation and utilization processes, which involves the management, implementation and utilization of the subject [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The dual-carbon micro-renewal of Changhua Street not only requires a suitable spatial design, but also guidance in the entire decision making, design, implementation and utilization processes, which involves the management, implementation and utilization of the subject [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, participants may need to possess a certain degree of ecological knowledge to play roles in diverse mangrove forest management activities, such as practicing conservation or restoration activities or sharing related information in a decision-making process. Insufficient ecological knowledge can cause hesitation among participants to take part in the project [25,28,82]. Furthermore, participants' expected benefits of participation may also help promote participation in the environmental CSR project.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…In the case of having a natural conservation project as a CSR, Raposo et al [25] found that a lack of relevant knowledge and capability can have a negative impact on the willingness to participate in water conservation. Chen and Liu [28] concluded that it is difficult for citizens who have insufficient ecological knowledge to respond to ecological conservation. Thus, they are likely to hesitate to participate in CSR projects.…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized by porosity and high specific surface area (which is conducive to the growth and reproduction of microorganisms), can effectively improve compost compaction and ventilation, retain compost nutrients, slow the release of compost gases, strengthen the retention of carbon and nitrogen elements, and reduce the ecological toxicity of heavy metals, antibiotics, and other pollutants in 10.3389/fmicb.2022.1084171 compost (Wang and Zeng, 2018;Akdeniz, 2019). With the recent advocacy for a dual-carbon target (Chen and Liu, 2022;Hao et al, 2022), the discharge of greenhouse gases such as CH 4 and N 2 O is also one of the problems that cannot be ignored in the composting of livestock and poultry manure and other nitrogen-rich organic waste. The loss of nitrogen not only decreases the quality of compost, but is also a source of environmental pollution.…”
Section: Introductionmentioning
confidence: 99%